Effect of thymol on the broiler chicken antioxidative defence system after sustained dietary thyme oil application. Issue 5 (3rd September 2019) - Placha, I.; Ocelova, V.; Chizzola, R.; Battelli, G.; Gai, F.; Bacova, K.; Faix, S.
ABSTRACT: 1. The purpose of this study was to examine if the concentration of thymol as the main compound of Thymus vulgaris essential oil (TEO) influenced the antioxidant defence system in broilers. 2. Twenty-four broiler chickens were randomly divided at the day of hatching into three dietary treatment groups (0%, 0.05% and 0.1%, w/w TEO) with eight birds in each and were fed until four weeks of age. 3. Thymol content in plasma, duodenal wall and breast muscle significantly increased when 0.1% of thyme oil was added to the diet ( P < 0.05). Thymol concentration in plasma significantly correlated with levels measured in the duodenal wall and feed (rs = 0.7857, P < 0.05; rs = 0.7647, P < 0.05). Superoxide dismutase (SOD) activity increased, and malondialdehyde (MDA) concentration decreased significantly ( P < 0.05) in blood from chickens fed 0.1% TEO supplementation. Although the thymol concentration did not significantly decrease MDA amounts in breast muscle, a declining trend was observed. 4. The trial data confirmed the efficient absorption of thymol from the digestive tract into the systemic circulation, but only traces were found in breast muscle. Thymol content was sufficient for expressing its antioxidant properties in blood, but its low content in breast muscle was insufficient to significantly affect lipid oxidation and fatty acid composition.